2011
DOI: 10.1603/en11114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Host Tree Condition on the Performance ofTetropium fuscum(Coleoptera: Cerambycidae)

Abstract: Tetropium fuscum (F.) attacks weakened Norway spruce, Picea abies (L.) Karst., in its native Europe and may colonize healthy spruce in Nova Scotia, Canada. We used manipulative field experiments to evaluate: 1) the development of T. fuscum on apparently healthy red spruce (Picea rubens Sarg.) in Nova Scotia; 2) the influence of red spruce physiological condition (healthy, girdled or cut) on T. fuscum performance; and 3) the impact of natural enemies and competitors on T. fuscum performance when developing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 31 publications
4
37
1
1
Order By: Relevance
“…We randomly assigned each tree to one of two tree condition treatments, girdled or healthy (unmanipulated), and to one of three groups representing different T. fuscum attack dates. To experimentally stress trees, we used a chainsaw to girdle trees 30 cm above the tree base, Ϸ2.5 cm deep into the phloem and outer sapwood, on 6 May (12 trees), 20 May (9 trees), or 3 June 2009 (9 trees), similar to Flaherty et al (2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We randomly assigned each tree to one of two tree condition treatments, girdled or healthy (unmanipulated), and to one of three groups representing different T. fuscum attack dates. To experimentally stress trees, we used a chainsaw to girdle trees 30 cm above the tree base, Ϸ2.5 cm deep into the phloem and outer sapwood, on 6 May (12 trees), 20 May (9 trees), or 3 June 2009 (9 trees), similar to Flaherty et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…We protected either the top or the bottom group of eggs (randomly selected) from natural enemies and competitors by fastening a Þne-mesh cage (Flaherty et al 2011) 17.5 cm above and below the eggs on each tree. We fastened cages on each tree in early May, before girdling, and they remained on trees until the tree was cut or until 14 April 2010, when they were replaced with emergence cages (see T. fuscum Survival, Size, and Development).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beetle is able to disperse via flight and by human-assisted dispersal through the movement of infested spruce products; therefore, the movement of high-risk forest products is restricted by ministerial order (Canadian Food Inspection Agency 2014). Further research on host preference by T. fuscum has shown that the beetle prefers stressed trees over healthy trees (Flaherty et al 2011(Flaherty et al , 2013, thus lowering the risk profile associated with healthy red spruce, and this has had a bearing on the decision of Canadian Food Inspection Agency to shift to a containment strategy (Canadian Food Inspection Agency 2014).…”
Section: Native Insect-fungus Symbiosesmentioning
confidence: 99%
“…Beetles of the genus Tetropium inhabit weakened, dying and dead trees, but they are not classified as dangerous forest pests (three species are classified as quarantine pests) [22,24,25]. Adults of T. fuscum appear in the Białowieża Forest around mid-May, and the last specimens can be found even in July.…”
Section: Introductionmentioning
confidence: 99%